Pemanfaatan Minyak Atsiri Daun Sirih (Piper Betle Linn) Sebagai Anti Nyamuk - Deki Gunawan; Rina Kurniaty (Journal of Pharmaceutical and Health Research, 2021)
Betel leaf (Piper betle Linn) is a plant that is widely known by the people of Indonesia, contains phenolic compounds and their derivatives which reaches 30% in extracts and essential oils, and at a concentration of 100 ppm it can kill mosquito larvae based on insecticidal activity. This study aims to utilize betel leaf essential oil, which was obtained by steam distillation method in the form of a spray dosage form and to find out at what concentration the betel leaf essential oil can be used as an insect repellent. This research is a laboratory experiment, there are 3 formulas of mosquito repellent spray (F1, F2 and F3) with a concentration of 13%, 15%, and 17%. The tests carried out on the anti-mosquito spray preparation were organoleptic tests and tests the effectiveness of the preparations against ten adult mosquitoes. Anti-mosquito spray preparation with a concentration of 17% betel leaf essential oil which is more effective at repelling and killing mosquitoes. Further research can develop the use of betel leaf essential oil with variations in different concentrations, or in combination with other active ingredients as mosquito repellent